العلاقة بين مناخ الفصل الدراسي ومهارة الاستماع لدى الطالبات في الصف الثالث المتوسط بمعهد سبيل المؤمنين تانجونج آنوم ديلي سردانج - Zaky, Ahmad; Jamaluddin, Muhajirah Binti; Sari, Asnilam (Lembaga Yasin AlSys, 2024)
Class climate is one of the factors that affect Arabic language learning, especially listening proficiency. This factor will become a bigger problem when not given full attention to it. This research presents the results of an empirical study on the correlation of classroom climate with listening proficiency. This study aims to determine the correlation between classroom climate and Arabic listening proficiency in class IX Tsanawiyah MTs Sabilul Mukminin Tanjung Anom Deli Serdang students. This research is a type of research using a quantitative approach. The data analysis technique to test the hypothesis is done by statistical calculation of spearman rank correlation. Will this research answer the hypothesis of this study? This will be answered after the researcher analyzes the data using spearman rank correlation statistics because the data in this study is ordinal scale.